Assessment of Government-E-Marketplace (Gem) on Procurement Compared to Conventional Methods in A PSU - Special Ref to BHEL - Hyderabad - Pumps Division. (Global Journal of Management and Business Research, 2024)
Abstract not found
Keywords: purchase in PSU (public sector undertaking); BHEL GEM procurement